Relative bond-stock liquidity and capital structure choices - Nguyen, Trang; Alpert, Karen; Faff, Robert (Journal of Corporate Finance, 2021)
This paper investigates whether the relative liquidity of a firm's bonds versus its stock affects its capital structure choice. As capital structure decisions involve balancing the costs and benefits of different financing alternatives, the relative liquidity of bonds versus stock plausibly matters since a relative liquidity differential might lead to one financing option being materially (relatively) cheaper than the other. As predicted, we find some evidence that, other things being equal, firms with relatively more liquid bonds compared to stock have higher leverage. While the relationship between bond-stock relative liquidity and leverage is statistically significant, our evidence suggests that it comes with only modest economic importance.